2021
DOI: 10.1016/j.csbj.2021.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the tumor RBP-ncRNA circuits by integrating transcriptomics, interactomics and clinical data

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…MAGI2-AS3 genes known to bind RBPs have been reported. Jiang et al 31 have suggested that MAGI2-AS3 had high connections with RBPs and miRNAs in the pan-cancer network and the new role of a member of the pan-cancer RBP-ncRNA circuits hsa-miR-224-5p-MAGI2-AS3-MBNL2 in the EMT program. Subsequently, the abnormal expression of RBPs was closely correlated with the occurrence and development of malignant tumors; the RBP EIF4A3 was overexpressed in a considerable number of cancers and coordinated cell cycle and cell apoptosis 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…MAGI2-AS3 genes known to bind RBPs have been reported. Jiang et al 31 have suggested that MAGI2-AS3 had high connections with RBPs and miRNAs in the pan-cancer network and the new role of a member of the pan-cancer RBP-ncRNA circuits hsa-miR-224-5p-MAGI2-AS3-MBNL2 in the EMT program. Subsequently, the abnormal expression of RBPs was closely correlated with the occurrence and development of malignant tumors; the RBP EIF4A3 was overexpressed in a considerable number of cancers and coordinated cell cycle and cell apoptosis 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of elucidating the pathogenesis of cancer, thus designing better therapeutic interventions through the novel lens of RBP-ncRNA circuits. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…Since SR proteins cross-regulate shared target genes, including the transcripts of each other, and form a dense coordinated network [ 76 ], a systems biology approach can be applied to globally identify the most dysregulated SR protein–RNA circuits under cancer conditions. This complementary approach enables the researcher to simultaneously characterize all alterations in SR proteins and to balance their multifunctionality without being trapped into negligible details [ 77 , 78 ].…”
Section: Functional Mechanisms Of Sr Proteins In Cancermentioning
confidence: 99%